2016
DOI: 10.1038/srep36646
|View full text |Cite
|
Sign up to set email alerts
|

GR-independent down-modulation on GM-CSF bone marrow-derived dendritic cells by the selective glucocorticoid receptor modulator Compound A

Abstract: Dendritic cells (DC) initiate the adaptive immune response. Glucocorticoids (GCs) down-modulate the function of DC. Compound A (CpdA, (2-(4-acetoxyphenyl)-2-chloro-N-methyl-ethylammonium chloride) is a plant-derived GR-ligand with marked dissociative properties. We investigated the effects of CpdA on in vitro generated GM-CSF-conditioned bone marrow-derived DC (BMDC). CpdA-exposed BMDC exhibited low expression of cell-surface molecules and diminution of the release of proinflammatory cytokines upon LPS stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
3
10
0
1
Order By: Relevance
“…Percentages for each subset (29.2 vs. 61.6, respectively) were in agreement with previous reports [23,24]. Incubation with 2 mM Gal-8 for 18 h induced the expression of CD86 in both CD11c + BMDC subsets, whereas expression of CD80 was induced only in MHCII high /CD11b int cells (Fig.…”
Section: Gal-8 Induces DC Activationsupporting
confidence: 92%
See 1 more Smart Citation
“…Percentages for each subset (29.2 vs. 61.6, respectively) were in agreement with previous reports [23,24]. Incubation with 2 mM Gal-8 for 18 h induced the expression of CD86 in both CD11c + BMDC subsets, whereas expression of CD80 was induced only in MHCII high /CD11b int cells (Fig.…”
Section: Gal-8 Induces DC Activationsupporting
confidence: 92%
“…With the possibility that Gal-8 may stimulate APC to sustain T cell activation after priming, we investigated whether this lectin displayed a direct effect on DC function. BMDCs, differentiated in vitro from GM-CSF/IL-4 conditioned mice bone marrow cultures, constitute a DC model that has been largely used to study many aspects of APCs [19][20][21][22][23]. Recently, it has been demonstrated that CD11c + BMDC cultures comprise a heterogeneous population of DCs (GM-DC) and macrophages (GM-M) [24].…”
Section: Gal-8 Induces DC Activationmentioning
confidence: 99%
“…In order to understand whether the protective effect of eckol against acute hepatic injury was related to dendritic cells, we performed the immunohistochemical staining for CD11c, a commonly used and classical dendritic cell-specific marker [ 34 ]. As shown in Figure 5 , in the eckol-treated groups, more liver cells expressing CD11c were identified to infiltrate into the portal area and parenchyma of the liver, suggesting the dendritic cell recruitment activity of eckol might be responsible for the enhanced production of anti-inflammatory IL-10 in liver tissues, and therefore, might be a part of mechanisms underlying the protective effect of eckol against acute hepatic injury induced by CCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids affect gene expression by two main GR-dependent and -independent intracellular mechanisms that exert several biological effects. These differential mechanisms have fueled the interest in the study and development of new GR-ligands with dissociative properties combining GCs’ anti-inflammatory properties with a reduced side effect profile ( 175 , 176 ). These particular dissociated GR-ligands hold potential for their use in Th1-mediated immune disorders.…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 99%